Designing the Model of the Management of Mental Health Services - Rahbari, Shahrooz (2020)
Introduction: Having mental health is necessary for the growth and prosperity of humans and as a result of the growth of societies.Objectives: The purpose of this study was to design a mental health management model in Iran.Methods: In this exploratory study, a review study was first performed to analyze the current state of mental health services in Iran and the world. Countries were selected to compare mental health management with Iran in 6 domains. 311 faculty members with mental health were completed by completing a questionnaire with 50 items in the study. Using the factor analysis, the final model was explained. Results: The effective domains in Iranian mental health services management were named in 8 areas: Mental Health in Particular, Key Centers and Task-Shifting, Human Resources and Specialists Training, Psychological Services for Children and Adolescents, Financial Resources and Hospital Services, Mental Health in PHC and Primary medical services, Policy-Making and Human Rights, Monitoring and Control, Community-Based Services. Conclusions: The proposed model of mental health services management in Iran consists of 8 domains, which is a comprehensive and multidimensional concept. Paying attention to its factors can lead to the successful management of mental health services in Iran.